Participation of Higher Secondary School Teachers in School Administration (Global Journal of Human-Social Science, 2016)
Teacher play a important role in school both academically and by participating in school administration for ensuring quality education for student. The efficiency of the school system can be ensured not by providing only a magnificent building to it, but by organizing and administering it on ideal lines in every way. A good building is just one small factor. There is the human element in the form of pupils, teachers and administrators without which the body of a school is incomplete and even inconceivable. Although the structure of a school is also raised by bricks and mortar but the more important things about school are the ideas, aims and the spirit behind its structure. Organization of a school is much more than a mere structure. Its administration is also not to be on the same pattern as the administration of a factory or a department The teacher's job is a challenge for even the most capable. Its duties and function are unlimited in number. The present investigation was undertaken to study the Participation of Higher Secondary School Teachers in School Administration'. The researcher selected 100 teachers from 12 higher secondary schools of Jalpaiguri district.
Keywords: participation; administration; planning; organization; co-ordination; educational administration; school administration; secondary school teacher; com